Analysis of factors ifluencing consumer purchase intention on electric motorcycle - Kariathi, Ni Nyoman Trida; Mayasari, Iin (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
Air pollution is worsening due to the increasing emissions produced by motor vehicles each year. The consumption of vehicle fuels releases various pollutants into the atmosphere, necessitating efforts to control air pollution to prevent the emissions from worsening. Electric motorcycles represent an environmentally beneficial innovation. With electric motorcycles, it is hoped that pollution resulting from carbon emissions will decrease, providing a solution to future energy scarcity. Electric motorcycles have an advantage over conventional motorcycles in that they can reduce emissions, as they do not emit gas. However, the use of electric motorcycles has not yet achieved optimal results. Therefore, this research aims to determine the influence of Subjective Norms, Perceived Behavioral Control, and Environmental concerns on Consumer Attitudes towards Purchase Intention of electric motorcycles. Data was collected by engaging 167 civil servants in Bali Province with an online survey to test four hypotheses. Analysis and hypothesis testing were conducted using the SmartPLS software. This research findings that all hypotheses are supported; Subjective Norm, Perceived Behavioral Control, and Environmental Concern significantly influence Consumer Attitude toward Purchase Intention of electric motorcycles. It is important to consider these factors and develop a holistic strategy to promote Purchase Intention for electric motorcycles.